2004
DOI: 10.3390/s40400037
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Gradient Effect on Gas Discrimination Power of a Metal-Oxide Thin-Film Sensor Microarray

Abstract: Abstract:The paper presents results concerning the effect of spatial inhomogeneous operating temperature on the gas discrimination power of a gas-sensor microarray, with the latter based on a thin SnO 2 film employed in the KAMINA electronic nose. Three different temperature distributions over the substrate are discussed: a nearly homogeneous one and two temperature gradients, equal to approx. 3.3 o C/mm and 6.7 o C/mm, applied across the sensor elements (segments) of the array. The gas discrimination power of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 10 publications
0
52
0
Order By: Relevance
“…In this case, the sensors of the array have a single signal type while the variation of both the properties and output characteristics is achieved using a differentiation of either sensor internal characteristics or external working conditions [2]. The most widely used arrays of this type are based on semiconductor chemiresistors [9]. Such a chemiresistor is usually formed on an insulating substrate by applying the electrodes over/under a gas-sensitive semiconductor such as a metal oxide.…”
Section: The "Electronic Nose" Device Based On Multisensorarraymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the sensors of the array have a single signal type while the variation of both the properties and output characteristics is achieved using a differentiation of either sensor internal characteristics or external working conditions [2]. The most widely used arrays of this type are based on semiconductor chemiresistors [9]. Such a chemiresistor is usually formed on an insulating substrate by applying the electrodes over/under a gas-sensitive semiconductor such as a metal oxide.…”
Section: The "Electronic Nose" Device Based On Multisensorarraymentioning
confidence: 99%
“…The chip is housed into a 120pin package (PGA-120, Kyocera Co., Japan) on ceramic columns [11]. To make a differentiation of the sensor segment properties over array the substrate has been inhomogeneously heated [9] so that only one side of the chip substrate has been secured on the columns by ceramic adhesive. Electrical connections to the electrodes, heaters and thermoresistors have been made by Au wires, 38 mkm thick, by ultrasonic welding.…”
Section: The "Electronic Nose" Device Based On Multisensorarraymentioning
confidence: 99%
“…The multisensor microarray employed in this study was fabricated according to earlier reported protocols [9][10][11]. In brief, the SnO 2 :Pt film was deposited by r.f.…”
Section: The Multisensor Microarray and Data Acquisitionmentioning
confidence: 99%
“…Therefore, they are not applicable for exacting analysis of gas mixtures. This is the reason that other means are necessary like gas sensor arrays of MOGs [1,2] or the operation of MOGs in a thermo-cyclic mode. The simultaneous sampling of the conductance values, gained from this operation mode, leads to so-called "conduction over time profiles" (CTPs) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%